Exploring the role and importance of post-disaster events in rural communities. (October 2015) - Sanders, Dale; Laing, Jennifer; Frost, Warwick
Abstract: A series of events is often held in the wake of natural disasters in rural communities, as a tool to assist in recovery. While this phenomenon is increasingly ubiquitous, there have been few studies which acknowledge this, and none to date that examine the types of events that assist disaster recovery, the roles they play and their importance in this process. This exploratory study aims to fill this gap using a case study of 87 events held after the Black Saturday fires in Victoria, Australia, in 2009. Findings suggest that there are eight main types of events held after a natural disaster – fundraising events, grieving events, community information sessions, community rebuilding events, re-openings, VIP visits, commemorations and thanksgiving events – and that these events perform different roles in disaster recovery. A portfolio of events might be usefully employed to combat disaster fatigue, through scheduling different types of events at different times. Highlights: Events are often staged in the wake of natural disasters in rural areas. The aim of these events is generally to assist the recovery of rural communities. This study examines the role and importance of events in the recovery process. Eight types of events were identified that are commonly staged post-disaster. A portfolio of events might be a useful strategy to combat disaster fatigue.